Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions

Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy

Energetic and exergetic performance of NH3-H2O-based absorption refrigeration cycle: effect of operating factor - Takalkar, Gorakshnath Dadabhau; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (International Journal of Exergy, 2020)
One of the major objectives while designing the vapour absorption refrigeration system (VARS) is to acquire better performance within the accessible heat source and sink temperature limit. In this paper, attempts are made to identify the temperature limit for the optimisation of a single stage ammonia refrigeration system (AAR) by performing a thermodynamic analysis. To estimate the potential of utilisation of low-grade heat energy, operating factor (R) is considered towards optimising the energetic (COP) and exergetic COP (ECOP). The simulated COP and ECOP results are expended to predict the feasibility and optimum operating region for an AAR cycle in terms of theRand various operating temperatures such asT(gen),T-abs,T-cond,T-e. The operating factorRcovers a wide range of applications i.e., from deep-freezing (253.15 K) to air conditioning (283.15 K) and from water-cooling (303.15 K) to air cooling (318.15 K).
Keywords: AAR; ammonia absorption refrigeration; cold storage; exergy; operating factor; solar energy

Thermodynamic analysis and experimental validation of multi-composition ammonia liquor absorption engine cycle for power generation - Satpute, Satchidanand R.; Takalkar, Gorakshnath; Mali, Nilesh; Bhagwat, Sunil (International Journal of Energy Research, 2020)
Energy conservation, utilization, and effective integration are of utmost importance for future sustenance. Accordingly, this work focuses on the generation of power from the low-grade temperature below 150 degrees C. A proposed novel multi-composition ammonia liquor absorption engine (MALAE) power cycle can be used toward the above purpose by supplying renewable energy obtained from low concentration type solar collectors. Proposed MALAE power cycle minimizes heal loss due to heat recovery and uses high purity NH3 vapors to expand through the isentropic turbine. MALAE power system is modeled and simulated using NH3-H2O as a working fluid for a reboiler temperature of 115 degrees C. The purpose of this work is to simulate the proposed MALAE power cycle with the distillation column and two solution heat exchanger (SHE). MALAE modeling and simulation is accomplished in SCILAB software. The simulation outcome is validated with the pilot-scale 5 kW experimental setup and validation showed +/- 5% deviation. A comparison of MALAE cycle with published cycles signifies higher efficiency of MALAE cycle toward the utilization of low-grade energy from a temperature range of 100 degrees C to 150 degrees C. Finally, detailed parametric analysis of MALAE cycle efficiency is presented in terms of number of plates, distillation pressure and vapor flowrate, absorber temperature, pressure partial condenser temperature, and heat loads.
Keywords: absorption power cycle; ammonia water; low-temperature heat source; solar energy; Thermal Efficiency

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting

Interface-centric strategies in kesterite solar cells: addressing challenges, solutions, and future directions for efficient solar-harvesting technologies - Jagadish, Kusuma; Rahane, Ganesh K.; Kumar, Boddeda Sai; Borkar, Durgesh R.; Chordiya, Kalyani; Kavanagh, Sean R.; Roy, Anurag; Debnath, Tushar; Kolekar, Sadhu; Kahaly, Mousumi Upadhyay; Mali, Sawanta S.; Pal, Shovon; et al. (SMALL, 2024)
Keywords: band engineering; Defects; interface loss mechanism; kesterites; recombination control; solar energy

Visible-light-driven photocatalytic glycerol oxidation to value-added and highly selective glyceric/lactic acid - Kulkarni-Sambhare, Mukta; Salgaonkar, Kranti N.; Saha, Avishek; Gopinath, Chinnakonda S. (ChemiCatChem, 2025)
Achieving economical and sustainable artificial photosynthesis (APS) in direct sunlight for liquid fuel production with high efficiency remains an important challenge. A major obstacle in the photoelectrochemical (PEC) oxidation of organic compounds is attaining high selectivity with the desired product(s). This study introduces a novel strategy by integrating BiVO4 quantum dots (BVQDs), structurally and electronically, into the nanopores of commercial TiO2 (BVT for BVQDs integrated in pores of TiO2) to improve solar-driven photocatalysis. The band gap of the BVT photoanode decreases to 2.53 eV as compared to pure TiO2 (3.2 eV), which enhances visible light absorption and charge separation. BVT with Pt as a co-catalyst acts as an APS system, which selectively oxidizes glycerol into lactic acid (100% selectivity at 1 mM glycerol) and glyceric acid (98% selectivity at 100 mM), while simultaneously generating green hydrogen. Selectivity of the product can be further controlled by anaerobic or aerobic conditions as well as the length of the reaction time. Direct integration of BVQDs into TiO2 mesopores significantly enhances charge separation as well as utilization at redox sites. Current work provides key insights into optimizing photocatalytic conditions for highly selective value-added chemical production, which highlights the sustainability and efficacy of TiO2-based semiconductors with quantum dot integration.
Keywords: energy conversion; Energy storage; Photocatalysis; Quantum material; solar energy